The Effect of Price and Promotion on Property Purchasing Decisions at PT Kawanua Housing Development in Tomohon City - Lumain, Erin Erika; Tumbel, Tinneke M; Rogahang, Joula J. (Productivity, 2024)
This research focuses on understanding how consumers' perceptions of price and promotion can influence their decisions in property purchases. The study aims to analyze the impact of price and promotion on property purchase decisions at PT Pembangunan Perumahan Kawanua in the city of Tomohon. The research method used is quantitative, with the population drawn from consumers who are either property owners or still in the process of purchasing. Based on the results of statistical tests, the price variable with a calculated t-value of 25.069 exceeds the tabulated t-value (1.984) at a significance level of 0.01, which is lower than alpha (0.05). The promotion variable with a calculated t-value of 6.439 exceeds the tabulated t-value (1.984) at a significance level of 0.01, which is lower than alpha (0.05). We can conclude that the promotion variable (X2) has a significant impact on purchase decisions. Based on the results of the F-test, the calculated F-value is 737.081 with a significance level of 0.000. Therefore, the price and promotion variables together have a positive and significant impact on purchase decisions.